Clinical and laboratory findings in a series of subacute sclerosing panencephalitis - Anlar, Banu; Yalaz, Kalbiye; Ustaçelebi, Şemsettin (The Turkish Journal of Pediatrics, 1988)
Subacute sclerosing panencephalitis is a chronic neurologic disorder usually presenting with mental deterioration and myoclonus and progressing to coma and death. Measles antibodies in cerebrospinal fluid (CSF) and serum, EEG, histopathologic findings in brain and computerized tomography (CT) are important elements in diagnosis. In this paper, the clinical manifestations and laboratory findings of our series comprising 395 patients are reported. Myoclonus and mental deterioration were the most frequently observed symptoms. EEG, especially if diazepam is administered intravenously during the recording, is helpful in the diagnosis. Measles antibodies in CSF can be found at low levels even with advanced disease. Cortical atrophy or normal scan are the most frequent findings on CT.
Keywords: subacute sclerosing panencephalitis; slow virus disease; measles